Intermediate state representation approach to physical properties of molecular electron-detached states - I. Theory and implementation - Dempwolff, Adrian; Paul, Alexander C.; Belogolova, Alexandra M.; Trofimov, Alexander B.; Dreuw, Andreas (The journal of chemical physics, 2020)
The third-order non-Dyson algebraic-diagrammatic construction approach to the electron propagator [IP-ADC(3)] is extended using the intermediate state representation (ISR) formalism, allowing the wave functions and properties of molecular states with detached electron to be studied. The second-order ISR equations [ISR(2)] for the one-particle (transition) density matrix have been derived and implemented in the Q-CHEM program. The approach is completely general and enables evaluation of arbitrary one-particle operators and interpretation of electron detachment processes in terms of density-based quantities. The IP-ADC(3)/ISR(2) equations were implemented for ŜzŜzŜz-adapted intermediate states, allowing open-shell molecules to be studied using unrestricted Hartree-Fock references. As a first test for computations of ground state properties, dipole moments of various closed- and open-shell molecules have been computed by means of electron detachment from the corresponding anions. The results are in good agreement with experimental data. The potential of IP-ADC(3)/ISR(2) for the interpretation of photoelectron spectra is demonstrated for the galvinoxyl free radical.
Gesehen am 14.04.2020